Development And Evaluation of In-Situ Nasal Gel Formulations of Nanosized Transferosomal Triptans - Mehta, Farhad F; Patel, Jitendra; Barot, Shruti; Patel, Shital; Agrawal, Krutika; Purohit, Debashis; Sarkar, Bishal; Bagade, Om M. (Journal of Neonatal Surgery, 2025)
The study's goal was to create an intranasal transferosomal mucoadhesive gel that would increase the bioavailability of zolmitriptan. Reverse phase evaporation was used to create zolmitriptin-loaded transferosomes, which were then characterised for a number of factors, including vesicle diameter, percent entrapment efficiency (%EE), and in vitro release. Carrageenan, poloxamer 188, and carbopol 934 were used in different ratios to create the in-situ gels, which were then evaluated for rheological characteristics, mucoadhesive strength, and gelation temperature. The produced transferosomes showed sustained drug release over 8 hours, mean diameters of 213.7 ± 1.56 to 508.5 ± 3.75, and percent entrapment efficiencies (%EE) ranging from 49.2 ± 1.24 to 94.3 ± 3.87. Using carrageenan as a mucoadhesive polymer, the best formulae were added to Carbopol 934, poloxamer 188, and carrageenan-based in-situ gel. The in-situ gel of zolmitriptan-loaded nano-transferosomes was created as a promising non-invasive drug delivery method based on improving the bioavailability and drug release